Targeted glycophagy ATG8 therapy reverses diabetic heart disease in mice and in human engineered cardiac tissues - Mellor, K M; Varma, U; Koutsifeli, P; Curl, C L; Janssens, J V; Daniels, L J; Bernasochi, G B; Raaijmakers, A J A; Annandale, M; Li, X; James, S L; Taylor, D J; et al. (bioRxiv, 2025)
Diabetic heart disease is highly prevalent and is associated with the early development of impaired diastolic relaxation. The mechanisms of diabetic heart disease are poorly understood and it is a condition for which there are no targeted therapies. Recently, disrupted glycogen-autophagy (glycophagy) and glycogen accumulation have been identified in the diabetic heart. Glycophagy involves glycogen receptor binding and linking with an ATG8 protein to locate and degrade glycogen within an intracellular phago-lysosome. Here we show that glycogen receptor protein STBD1 (starch-binding-domain-protein-1) is mobilized early in the cardiac glycogen response to metabolic challenge , and that deficiency of a specific ATG8 family protein, Gabarapl1 (γ-aminobutyric-acid-receptor-associated-protein-like-1) is associated with diastolic dysfunction in diabetes. Gabarapl1 gene delivery treatment remediated cardiomyocyte and cardiac diastolic dysfunction in type 2 diabetic mice and diastolic performance of 'diabetic' human iPSC-derived cardiac organoids. We identify glycophagy dysregulation as a mechanism and potential treatment target for diabetic heart disease.